Implementation Of Input Tax Prepopulated Data And Vat E-Spt In Increasing Value Added Tax Reporting Agency Tax Registered At Kpp Pratama Bulukumba - Rika Solihatun; Rustan Rustan; Agusdiwana Suarni (Universitas Muhammadiyah Makassar, 2022)
Prepopulated Input Tax Data and Electronic Notification Letters (e-SPT) The PNN period is one part of the modernization process of Tax administration, so that taxpayers have the convenience of fulfilling and completing their obligations, so that the fulfillment of their tax obligations can be completed easily in their implementation, and the aim is to create an orderly and transparent tax administration. The purpose of this study is to determine the application of prepopulated input tax data and e-SPT Period of VAT in increasing the value added tax reporting of corporate taxpayers. The method used in this research is descriptive research type. To obtain the necessary data, the authors carried out data collection activities for 2018-2021, by interviewing Mr. Dwi Bagas Widianto as the System Administrator or the Data Quality Assurance Section. The results of this study indicate that the application of prepopulated tax data and e-SPT for the VAT period is very effective and efficient at KPP Pratama Bulukumba, it can be seen from the increase in Value Added Tax reporting and the use of the Prepopulated data system and e-SPT for the VAT period which is increasing every year. It is hoped that the Directorate General of Taxes and their regional offices should be able to improve their performance, including by providing counseling about the importance of paying taxes on time, and providing the best services, especially for taxpayers.